Multibeam Processing for Nautical Charts (Using CUBE and “Surface Filter” to enhance multibeam processing) - de Oliveira Junior, LCDR Aluizio Maciel; King Jeck, CDR Izabel (The International Hydrographic Review, 2009)
The Brazilian Navy Directorate of Hydrography and Navigation (DHN) performed extensive experiments during 2008 in order to find a reliable and efficient work flow for processing multibeam data to update its nautical charts. A work flow using CUBE (combined uncertainty and bathymetric estimator) and “Surface filter” tools demonstrated excellent results when compared to traditional processing methods. CUBE can enhance processing speed and highlight critical areas for navigation, in which a hydrographer’s careful analysis is required. The “Surface filter” can eliminate bad soundings, but still keeps a shoal biased surface to be represented in nautical charts.